Spirulina platensis Lacks Antitumor Effect against Solid Ehrlich Carcinoma in Female Mice - Waleed Barakat; Shimaa M. Elshazly; Amr A. A. Mahmoud (Advances in Pharmacological Sciences)
Spirulina is a blue-green alga used as a dietary supplement. It has been shown to possess anti-inflammatory, antioxidant, and hepatoprotective properties. This study was designed to evaluate the antitumor effect of spirulina (200 and 800 mg/kg) against a murine model of solid Ehrlich carcinoma compared to a standard chemotherapeutic drug, 5-fluorouracil (20 mg/kg). Untreated mice developed a palpable solid tumor after 13 days. Unlike fluorouracil, spirulina at the investigated two dose levels failed to exert any protective effect. In addition, spirulina did not potentiate the antitumor effect of fluorouracil when they were administered concurrently. Interestingly, their combined administration resulted in a dose-dependent increase in mortality. The present study demonstrates that spirulina lacks antitumor effect against this model of solid Ehrlich carcinoma and increased mortality when combined with fluorouracil. However, the implicated mechanism is still elusive.